PENGARUH DIFERENSIASI PRODUK DAN PERSEPSI KUALITAS PRODUK SERTA PROMOSI TERHADAP KEPUTUSAN PEMBELIAN TAHU JONTOR DI SAMARINDA - ADHI KAHFIADI; RAHMAWATI -; SRI WAHYUNI (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2016)
The purpose of this study was to determine whether the effect of product differentiation, perception of product quality and promotion influence on purchase decisions Tahu Jontor in Samarinda using multiple linear regression. The results of this study indicate variable product differentiation, perception of product quality and promotion significantly influence purchasing decisions. Rated R for 0988, which means that there is a very strong variable product differentiation, perception of product quality and promotion of their purchasing decisions. The coefficient of determination (R2) of 0976 means that the model is very good coefficient of determination. It shows that 97.6% purchase decision is influenced by three independent variables while the remaining 2.4% is influenced by other variables that are not in thoroughly. Based on t test, the results obtained that the variable product differentiation, perception of product quality and promotion of positive and significant influence on purchasing decisions. Keywords: product differentiation, perception of product quality, promotion and purchasing decisions